Papillon-Lefèvre syndrome: Report of a rare case - Amirreza Ahmadinia; Ahmad Moghareabed; Mozhgan Izadi (Isfahan University of Medical Sciences, 2013)
Introduction: Papillon-Lefèvre syndrome is a rare autosomal recessive disorder. This syndrome is characterized by palmoplantar hyperkeratosis, severe periodontal destruction and premature loss of primary and permanent teeth. The teeth erupt normally but due to the severe alveolar bone loss in both deciduous and permanent dentitions teeth are exfoliated within two or three years after eruption and by the age of 15 or 17 patients are usually edentulous. The identified genetic defect in this syndrome involves a mutation in the gene encoding cathepsin C. An increased susceptibility to infection has also been reported in patient with this syndrome.Case Report: A 15-year-old girl was referred to the dental clinic, complaining of the mobility of permanent teeth. The patient had lost all the permanent teeth except for teeth 13, 14, 17, 23, 27, 37, 43, 44 and 47. The third molars were impacted. The patient had advanced periodontal disease and all the teeth had severe mobility. There was hyperkeratosis at the palms and soles. She did not report a history of recurrent skin infections and liver abscesses. Complete blood count and liver tests were within the normal limits.Conclusion: Due to periodontal disease the dentists are often the first to diagnose this syndrome. Early diagnosis of Papillon-Lefèvre syndrome can help preserve the permanent teeth by early institution of treatment, using a multidisciplinary approach. Dental treatment includes extraction of all deciduous teeth, professional prophylaxis, conventional periodontal therapy, systemic antibiotics, oral retinoids, complete dentures and implants.Key words: Aggressive periodontitis, Cathepsin C, Hyperkeratosis, Papillon-Lefèvre syndromeKey words: Aggressive periodontitis, Cathepsin C, Hyperkeratosis, Papillon-Lefèvre syndrome